Design considerations of non-axisymmetric exhausts for large civil aero-engines - Hueso Rebassa, Josep; MacManus, David G.; Goulos, Ioannis; Tejero, Fernando (American Institute of Aeronautics and Astronautics (AIAA), 2023)
In order to reduce fuel consumption, the next generation of aero-engines are expected to operate with higher bypass ratios and lower fan pressure ratios. This will improve the propulsive efficiency of the power plant and reduce specific fuel consumption. Higher bypass ratios will be mostly accommodated with larger fan diameters. However, this will increase the size and mass of the powerplant, which could penalise the overall aircraft drag and erode some of the aero-engine cycle benefits. In addition, future configurations may require more close-coupled installations with the airframe due to structural and ground clearance requirements. This tendency may further exacerbate the adverse aerodynamic installation effects. A better integration of UHBR aero-engines with the airframe could be achieved with non-axisymmetric separate-jet exhausts. Non-axisymmetric configurations of the bypass nozzle can improve the performance of the aircraft by mitigating some of the penalising aerodynamic effects induced by the installation of the power plant. In this context, three-dimensional configurations of exhaust systems are parametrised and integrated with the propulsion system through a refined control of the geometry. The power plant is installed on the NASA Common Research Model and assessed with CFD. The design of non-axisymmetric exhausts is embedded in a relatively low-cost optimisation process. The method is based on response surface models and targets the optimisation of the aircraft net vehicle force for different design concepts of non-axisymmetric exhaust systems and several installation configuration. It is concluded that the optimisation of installed non-axisymmetric exhausts can benefit the overall aircraft net vehicle force between 0.5-0.9% of the engine nominal thrust, depending on the installation position.